Loss-of-function variants in the schizophrenia risk gene SETD1A alter neuronal network activity in human neurons through the cAMP/PKA pathway - Shan Wang; Jon-Ruben van Rhijn; Ibrahim Akkouh; Naoki Kogo; Nadine Maas; Anna Bleeck; Irene Santisteban Ortiz; Elly Lewerissa; Ka Man Wu; Chantal Schoenmaker; Srdjan Djurovic; Hans van Bokhoven; et al. (Cell Reports, 2022)
Summary: Heterozygous loss-of-function (LoF) mutations in SETD1A, which encodes a subunit of histone H3 lysine 4 methyltransferase, cause a neurodevelopmental syndrome and increase the risk for schizophrenia. Using CRISPR-Cas9, we generate excitatory/inhibitory neuronal networks from human induced pluripotent stem cells with a SETD1A heterozygous LoF mutation (SETD1A+/−). Our data show that SETD1A haploinsufficiency results in morphologically increased dendritic complexity and functionally increased bursting activity. This network phenotype is primarily driven by SETD1A haploinsufficiency in glutamatergic neurons. In accordance with the functional changes, transcriptomic profiling reveals perturbations in gene sets associated with glutamatergic synaptic function. At the molecular level, we identify specific changes in the cyclic AMP (cAMP)/Protein Kinase A pathway pointing toward a hyperactive cAMP pathway in SETD1A+/− neurons. Finally, by pharmacologically targeting the cAMP pathway, we are able to rescue the network deficits in SETD1A+/− cultures. Our results demonstrate a link between SETD1A and the cAMP-dependent pathway in human neurons.